Patient education to support self-management of patients with mental illness - Hätönen, Heli (fi=Turun yliopisto|en=University of Turku|, 2010)
This study explores areas which need to be improved to develop the quality of patient education to support self-management of patients with mental illness in psychiatric hospitals. The study was conducted in five phases during the period 2000 – 2007. First, patients‘ (n = 313) satisfaction with patient education were investigated. Second, patients' (n = 51) experiences of patient education were explored. Third, a national survey was conducted to investigate realisation of patient education from the staff (n = 55) viewpoint. Fourth, outcomes of patient education were investigated by evaluating the impacts of different patient education methods on patients‘ (n = 311) attitudes towards medication, knowledge level and importance of information. Fifth, patients‘ (n = 16) perceptions of different patient education methods were explored. Patients reported poor satisfaction with patient education (Phase I), and they have considerable need to receive information during their hospital stay (Phase II). Described by staff, the content of patient education covered almost all informational areas investigated. However, discrepancies related to the realisation of patient education were found. (Phase III.) Evaluation of different patient education methods indicate that patients derived benefits from structured patient education with supportive methods (Phase IV) and patients also perceived that these methods supported their information receiving (Phase V). In order to improve the quality of patient education to support self-management of patients with mental illness patient education should be systematically and individually provided to all patients by using different educational methods. Realisation of this should be ensured by providing written instructions, improving nurses‘ knowledge and skills as well ensuring operating conditions.